Pure zwitterionic dual-network hydrogel coating as well as preparation method and application thereof
By preparing pure zwitterionic double network hydrogel coatings on the surface of biomedical equipment, using electrostatic interaction and chain tangling mechanisms, the thrombosis problem of existing coatings during blood contact is solved, and mechanical properties and anti-fouling ability are improved, and stable preparation on the surface of materials such as polyvinyl chloride is achieved.
Patent Information
- Application Number
- CN202411970407.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
Smart Images

Figure CN119746173A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogel coatings, and in particular relates to a pure zwitterionic double-network hydrogel coating and a preparation method and application thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Biomedical devices that come into contact with blood have been widely used in clinical practice. However, when the device surface comes into contact with blood, thrombotic inflammation and related infections are inevitably induced. It is generally believed that nonspecific protein adhesion is the "trigger" of biological contamination events, and hydrophilic surfaces have been shown to effectively resist protein adhesion. Therefore, in the field of medical devices, surface hydrophilization treatment is particularly important. Zwitterionic polymer molecules contain equal amounts of positive and negative charges at the same time, and are electrically neutral as a whole. Their surfaces can interact electrostatically with water to form a dense hydration layer, making them a strong candidate material for the preparation of hydrophilic coatings. Zwitterionic polymer coatings have been widely studied. However, the current surface-initiated atom transfer radical polymerization technology (SI-ATRP) has problems such as difficulty in removing metal catalysts, the need for inert gas protection, and difficulty in reusing monomers, which limits the practical application of polymer coatings.
[0004] Hydrogel coating is one of the effective methods for hydrophilic treatment, but traditional zwitterionic hydrogel coatings have problems such as low mechanical strength and weak long-term antifouling ability. Improving the mechanical properties of zwitterionic hydrogel coatings generally requires the introduction of non-zwitterionic components, which in turn sacrifices the antifouling ability. Therefore, it is crucial to use pure zwitterions to enhance the mechanical strength of zwitterionic hydrogels.
[0005] In addition, most medical catheter substrates are made of polymer materials such as polyvinyl chloride, polyurethane, and silicone rubber. The inert surfaces of these polymer materials have weak interactions with the hydrogel coating, which makes it difficult to prepare the hydrogel coating on the surfaces of these polymer materials and the prepared hydrogel coating has poor stability. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a pure zwitterionic double-network hydrogel coating and a preparation method and application thereof.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a pure zwitterionic double network hydrogel coating, comprising the following steps:
[0009] After the substrate to be treated is treated with plasma, it is immersed in a hydrophobic photoinitiator solution for a set time, and then taken out and excess hydrophobic photoinitiator is washed off to obtain a pretreated substrate;
[0010] The first network pSB pregel solution is covered on the surface of the pretreated substrate, and irradiated with ultraviolet light under deoxygenated conditions to form a pSB single network hydrogel coating on the surface of the substrate;
[0011] Then, the substrate is immersed in the second network pSB pregel solution, stored at low temperature and away from light for a set time, taken out, and irradiated with ultraviolet light under deoxygenated conditions to form a pSB double network hydrogel coating on the surface of the substrate;
[0012] In the first network pSB pregel solution, the concentration of SBMA (methacryloylethyl sulfobetaine) is 0.5-1.5M, the molar percentage of MBA (N,N-methylenebis(acrylamide)) in SBMA is 1-5%; the molar percentage of hydrophilic photoinitiator in SBMA is 0.05-0.2%;
[0013] In the second network pSB pregel solution, the concentration of SBMA is 2-5M, the molar percentage of MBA to SBMA is 0.05-0.15%, and the molar percentage of hydrophilic photoinitiator to SBMA is 0.005-0.02%.
[0014] In the present invention, a pure zwitterionic double network hydrogel with enhancement, toughening and swelling resistance is prepared by utilizing the electrostatic interaction between SBMA molecules and molecules. First, the PU matrix is immersed in an acetone solution of the hydrophobic photoinitiator 2959, at which time the photoinitiator 2959 diffuses into the swollen PU matrix to form a 2959-PU diffusion layer. Then, the SBMA monomer in the first network pSBMA precursor solution (high monomer concentration, low cross-linker ratio) spread on the surface penetrates into the 2959-PU diffusion layer. Under ultraviolet irradiation conditions, the pre-gel solution between the interface and the surface is polymerized simultaneously to form a firm pSBMA single network hydrogel coating (pSBSN-PU). Among them, the hydrophilic photoinitiator 1173 is used to form the pSB hydrogel, and the hydrophobic photoinitiator 2959 is used to mediate the polymerization of the SBMA monomers in the interface and form a entangled structure with the PU chain. The firm adhesion of the coating is attributed to the chain entanglement between pSBMA and the PU substrate.
[0015] Because of the oxygen inhibition effect, when a polymer is polymerized in the presence of oxygen, oxygen will react with the active intermediates of the polymer, thereby slowing down or stopping its polymerization rate.
[0016] When light curing in air, oxygen inhibition often results in the bottom layer of the coating being cured, while the surface is not cured and sticky. Oxygen inhibition can eventually lead to the appearance of a large number of oxidative structures such as hydroxyl, carbonyl, and peroxy groups on the surface of the coating, thus affecting the long-term stability of the coating and even the hardness, glossiness, and scratch resistance of the cured paint film. Therefore, when the reaction system is deoxygenated during polymerization under UV light.
[0017] Since the pre-gel solution contains photoinitiators, chemical cross-linking agents, etc., it is easy to cause the pre-gel solution to self-polymerize to form a thick gel layer when left at room temperature. Therefore, it is selected to be stored at low temperature and away from light.
[0018] pSB SN-PU was immersed in the second network pSBMA precursor solution (low monomer concentration, high cross-linker ratio). During this process, the pSB SN hydrogel swelled. Due to the strong electrostatic interaction between pSB and SBMA monomers, the pSB SN hydrogel absorbed a large amount of SBMA monomers and formed a loosely cross-linked second network under ultraviolet irradiation.
[0019] Thus, the pSBMA double network hydrogel coating (pSB DN-PU) was successfully synthesized, in which the chain entanglement of the first network and the second network pSB provided an effective energy dissipation mechanism for strengthening and toughening the hydrogel.
[0020] In some embodiments, the hydrophobic photoinitiator is photoinitiator 2959 or benzophenone.
[0021] Preferably, the concentration of the hydrophobic photoinitiator solution is 2-7wt%;
[0022] Further preferably, the concentration of the hydrophobic photoinitiator solution is 4-6wt%;
[0023] More preferably, the concentration of the hydrophobic photoinitiator solution is 5 wt %.
[0024] In some embodiments, the substrate to be treated is a medical device substrate.
[0025] Preferably, the substrate to be treated is a medical catheter substrate.
[0026] More preferably, the material of the medical guide rod substrate is polyvinyl chloride, polyurethane or silicone rubber.
[0027] In some embodiments, the substrate to be treated is immersed in the hydrophobic photoinitiator solution for 20-40 minutes.
[0028] Preferably, after the substrate to be treated is immersed in the hydrophobic photoinitiator solution, it is rinsed alternately with ethanol and deionized water to remove the hydrophobic photoinitiator physically attached to the surface of the substrate to be treated.
[0029] In some embodiments, in the first network pSB pregel solution, the concentration of SBMA is 0.7-1.2 M, the molar percentage of MBA to SBMA is 3-5%, and the molar percentage of hydrophilic photoinitiator to SBMA is 0.07-0.15%.
[0030] Preferably, in the first network pSB pre-gel solution, the concentration of SBMA is 1 M, the molar percentage of MBA to SBMA is 4%, and the molar percentage of hydrophilic photoinitiator to SBMA is 0.1%.
[0031] In some embodiments, the wavelength of the UV lamp is 250-350 nm, preferably 300-320 nm.
[0032] Preferably, the UV lamp irradiation time is 2-5 hours, preferably 3-4 hours.
[0033] In some embodiments, in the second network pSB pregel solution, the concentration of SBMA is 3-5M, the molar percentage of MBA to SBMA is 0.07-0.12%; and the molar percentage of hydrophilic photoinitiator to SBMA is 0.007-0.015%.
[0034] Preferably, in the second network pSB pregel solution, the concentration of SBMA is 3.5-4.5M, the molar percentage of MBA to SBMA is 0.09-0.12%; and the molar percentage of hydrophilic photoinitiator to SBMA is 0.009-0.012%.
[0035] Further preferably, in the second network pSB pregel solution, the concentration of SBMA is 4M, the molar percentage of MBA in SBMA is 0.01%, and the molar percentage of hydrophilic photoinitiator in SBMA is 0.01%.
[0036] In some embodiments, the storage temperature of the low-temperature storage setting time is below 5°C, and the storage time is 15-30 hours, preferably 20-25 hours.
[0037] In a second aspect, the present invention provides a pure zwitterionic double-network hydrogel coating prepared by the preparation method.
[0038] In a third aspect, the present invention provides a medical device having the pure zwitterionic double-network hydrogel coating attached to its surface.
[0039] In some embodiments, the medical device is a blood-contacting medical device.
[0040] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0041] The present invention utilizes the strong electrostatic interaction and chain entanglement of poly(sulfobetaine methacrylate) (pSBMA) to design a pure zwitterionic double network (pSB DN) hydrogel with high mechanical properties, and adopts the strategy of photoinitiator embedding and in situ polymerization to firmly adhere it to the surface of PU substrate.
[0042] The hydrogel coating is prepared by a simple two-step sequential polymerization method. First, the pSB precursor solution with low monomer concentration and high crosslinker ratio is polymerized by ultraviolet irradiation to form a tightly crosslinked single network brittle structure pSB SN hydrogel; when the prepared single network brittle structure pSB SN hydrogel is swollen in the second network precursor solution with high monomer concentration and low crosslinker ratio, a large amount of SBMA monomers penetrate into the first network, and then the monomers are polymerized by ultraviolet irradiation to form a pSB interpenetrating network to obtain a pSB DN hydrogel. In addition, since pSB has strong electrostatic interactions, the introduction of non-covalent bonds provides an effective energy dissipation mechanism for the hydrogel.
[0043] The first network is a tightly cross-linked rigid structure, and the second network is a loosely cross-linked flexible network. When the DN hydrogel coating is subjected to external force, the rigid network is usually destroyed to dissipate energy, while the flexible network maintains the integrity of the hydrogel matrix. The flexible network and the rigid network can work together to achieve a balance between rigidity and toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0045] Figure 1 Schematic diagram of the formation process and principle of pSBMA double network hydrogel in an embodiment of the present invention;
[0046] Figure 2 Schematic diagram of the preparation process of the pSBMA double network hydrogel coating in an embodiment of the present invention;
[0047] Figure 3 : AFR-FTIR images of the surfaces of bare PU, pSBMA single network and double network hydrogel coatings in the embodiments of the present invention;
[0048] Figure 4 Surface X-ray diffraction patterns of bare PU, pSBMA single network and double network hydrogel coatings in the embodiments of the present invention;
[0049] Figure 5 It is a high-resolution map of N elements on the surface of pSBMA single-network and double-network hydrogel coatings in an embodiment of the present invention;
[0050] Figure 6: are surface SEM images of bare PU, pSBMA single network and double network hydrogel coatings in the embodiments of the present invention;
[0051] Figure 7 are the apparent AFM images of bare PU, PU embedded with initiator 2959, and pSBMA single network and double network hydrogel coatings in the embodiments of the present invention;
[0052] Figure 8 is the water contact angle of bare PU and pSBMA double network hydrogel coating in the embodiment of the present invention;
[0053] Fig. 9 is the protein adsorption rate of bare PU, pSBMA single network and double network hydrogel coatings in the embodiments of the present invention;
[0054] Fig.10 Schematic diagram of water contact angles of bare PU, pSBMA single network and double network hydrogel coatings before and after ultrasonic destruction in an embodiment of the present invention. DETAILED DESCRIPTION
[0055] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0056] The present invention will be further described below in conjunction with the embodiments.
[0057] Example 1
[0058] Experimental steps:
[0059] (1) Preparation of zwitterionic double network hydrogel coating
[0060] The plasma-treated PU substrate was placed in a culture dish, immersed in a 5% (wt%) 2959 acetone solution for 30 min, taken out, and rinsed alternately with ethanol and deionized water to remove the photoinitiator 2959 physically attached to the surface, thereby obtaining an initiator-treated PU film named PU-2959.
[0061] PU-2959 was fixed in the mold using polyacrylate glue, and the first network pSB pregel solution (containing 1M SBMA, 4 mol% MBA (relative to SBMA) and 0.1 mol% photoinitiator 1173 (relative to SBMA)) was injected onto the PU-2959 substrate using a syringe, and then covered with a glass plate and clamped with tweezers. Under deoxygenated conditions, a UV lamp (302 nm, 6 W) was irradiated for 4 h to form a pSB single network hydrogel coating on the surface of the PU-2959 substrate, which was recorded as pSB SN-PU.
[0062] The prepared pSB SN-PU was immersed in a second network pSB pregel solution (containing 4MSBMA, 0.1 mol% MBA (relative to SBMA) and 0.01 mol% photoinitiator 1173 (relative to SBMA)) and stored at 4°C in the dark for 24 h. After being taken out, it was irradiated with an ultraviolet lamp (302 nm, 6 W) for 4 h under deoxygenated conditions to form a pSB double network hydrogel coating on the surface of the pSB SN-PU, which was recorded as pSB DN-PU.
[0063] (2) Surface chemical composition of zwitterionic double network hydrogel coating
[0064] The chemical compositions of the surfaces of bare PU, pSB SN-PU and pSB DN-PU were investigated by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) and X-ray photoelectron spectroscopy.
[0065] (3) Surface morphology of zwitterionic double network hydrogel coating
[0066] Scanning electron microscopy and atomic force microscopy were used to observe the surface morphology and roughness of bare PU, pSB SN-PU and pSB DN-PU. For scanning electron microscopy, bare PU, pSB SN-PU and pSB DN-PU were fully swollen in deionized water, and the samples were freeze-dried and sprayed with gold for 75s in a vacuum state, and then pasted to the conductive adhesive. The surface morphology of the samples was photographed and observed under the conditions of an acceleration voltage of 3KV and a working distance of 5-15mm. For atomic force microscopy, bare PU, pSB SN-PU and pSB DN-PU were immersed in deionized water to remove impurities, vacuum dried, and placed under an atomic force microscope for observation. The corresponding two-dimensional and three-dimensional AFM images and roughness were obtained using Gwyddion software.
[0067] (4) Anti-protein adhesion of zwitterionic double network hydrogel coating
[0068] The BCA reagent method was used to evaluate the anti-protein adhesion ability of the coating. 0.5 mL of BSA protein solution (5 mg / mL) was added to the surface of bare PU, pSB SN-PU and pSB DN-PU and incubated at 37°C for 90 min. After incubation, all samples were taken out and gently washed with PBS to remove physically attached proteins. All samples were soaked in 2% SDS solution and the adsorbed proteins were dissociated by ultrasonic treatment for 30 min. Subsequently, 100 μL of protein solution was aspirated, and then according to the instructions of the kit, a quantitative amount of BCA reagent was added to react at 37°C for 2 h, and the absorbance value at 562 nm was tested using a multifunctional microplate reader. Each sample was tested five times. Among them, the bare PU substrate was used as the control group, and normalization was performed to evaluate the anti-protein adsorption performance of other sample surfaces.
[0069] (5) Durability of zwitterionic double network hydrogel coating
[0070] Bare PU, pSB SN-PU and pSB DN-PU were placed in 20 mL of PBS buffer and then treated by ultrasound (300 W) in an ice ethanol bath for 1 hour. The water contact angles of all samples were measured before and after ultrasound treatment for 1 hour.
[0071] Test results:
[0072] (1) Design of zwitterionic double network hydrogels
[0073] Double-network hydrogels have been shown to achieve a balance between high-strength mechanical energy and toughness by regulating intramolecular / intermolecular interactions or the structure of the two networks. Pure zwitterionic components ensure the excellent antifouling properties of the hydrogels.
[0074] In the present invention, an enhanced, toughened and anti-swelling pure zwitterionic double network hydrogel is prepared by utilizing the electrostatic interactions within and between SBMA molecules.
[0075] pSB DN hydrogels were prepared by a two-step sequential polymerization method ( Figure 1 As shown), firstly, a pSB precursor solution with a low monomer concentration and a high cross-linking agent ratio is polymerized by ultraviolet irradiation to form a tightly cross-linked single-network brittle structure pSB SN hydrogel;
[0076] When the prepared single-network brittle structure pSB SN hydrogel swells in the second network precursor solution with high monomer concentration and low crosslinker ratio, a large amount of SBMA monomers penetrate into the first network, and then the monomers polymerize under ultraviolet irradiation to form a pSB interpenetrating network to obtain a pSB DN hydrogel. In addition, since pSB has strong electrostatic interactions, the introduction of non-covalent bonds provides an effective energy dissipation mechanism for the hydrogel.
[0077] (2) Preparation of zwitterionic double network hydrogel coating
[0078] The strategy of photoinitiator embedding and in-situ polymerization was used to improve the interfacial bonding strength between the hydrogel layer and the PU substrate. Figure 2As shown, first the PU matrix is immersed in an acetone solution of the hydrophobic photoinitiator 2959, at which time the photoinitiator 2959 diffuses into the swollen PU matrix to form a 2959-PU diffusion layer. Then, the SBMA monomer in the first network pSBMA precursor solution (high monomer concentration, low crosslinker ratio) spread on the surface penetrates into the 2959-PU diffusion layer. Under ultraviolet irradiation conditions, the pre-gel solution between the interface and the surface is polymerized simultaneously to form a firm pSBMA single network hydrogel coating (pSB SN-PU). Among them, the hydrophilic photoinitiator 1173 is used to form the pSB SN hydrogel, while the hydrophobic photoinitiator 2959 is used to mediate the polymerization of the SBMA monomers in the interface and form an entangled structure with the PU chain. The firm adhesion of the coating is attributed to the chain entanglement between pSBMA and the PU substrate.
[0079] pSB SN-PU was immersed in the second network pSBMA precursor solution (low monomer concentration, high cross-linker ratio). During this process, the pSB SN hydrogel swelled. Due to the strong electrostatic interaction between pSB and SBMA monomers, the pSB SN hydrogel absorbed a large amount of SBMA monomers and formed a loosely cross-linked second network under ultraviolet irradiation.
[0080] Thus, the pSBMA double network hydrogel coating (pSB DN-PU) was successfully synthesized, in which the chain entanglement of the first network and the second network pSB provided an effective energy dissipation mechanism for strengthening and toughening the hydrogel.
[0081] (3) Surface chemical composition of zwitterionic double network hydrogels
[0082] Figure 3 The AFR-FTIR results showed that compared with bare PU, the surface of pSB DN-PU had an additional 1035 cm -1 The asymmetric stretching vibration peak of S=O in the zwitterionic group indicates the successful grafting of pSB hydrogel.
[0083] Figure 4 The XPS results show that the bare PU surface only contains C, N, O and other elements, while the pSB SN-PU and pSB DN-PU surfaces have new S2p signal peaks. In addition, the binding energies of 402.2 eV (-N(CH3)3 + ) and 399.9eV (-NH) two characteristic peaks (such as Figure 5 Among them, -N(NH3)3 in pSB SN and pSB DN coatings belongs to pSB + The nitrogen percentage of the groups continued to rise, indicating the successful introduction of the second network pSB hydrogel coating.
[0084] (4) Surface morphology of zwitterionic double network hydrogel coating
[0085] The modification of the coating has a certain influence on the surface morphology of PU and will affect its antifouling ability. Figure 6 The SEM images of the bare PU showed that the surface was smooth and flat, while the surface modified by pSB SN hydrogel showed a uniform grooved surface with increased roughness. In contrast, the pSB DN hydrogel coating showed a flat surface with reduced roughness and a more compact structure, which was due to the chain entanglement between the introduced second network and the first network, resulting in a higher degree of cross-linking in the double network hydrogel coating.
[0086] Figure 7 The AFM images of the samples characterized the apparent roughness of each sample. Similarly, the surface of bare PU was smooth and flat, with a roughness of 6.9 nm. After being soaked in photoinitiator 2959, the roughness of PU increased slightly to 11.4 nm. After being modified with pSB single network hydrogel, the roughness of PU increased significantly to 177 nm, while the roughness of PU modified with pSB DN hydrogel decreased to 76 nm, indicating that the surface of pSB DN hydrogel was smoother, which was helpful to improve its antifouling ability.
[0087] (5) Functional characteristics of zwitterionic double network hydrogel coatings
[0088] Surface hydrophilicity is an important property of pSB hydrogel coatings and is also related to their antifouling ability. Figure 8 The water contact angle results showed that the water contact angle of the bare PU surface was 80.3±2.5°. Compared with the bare PU, the water contact angle of the pSB DN hydrogel coating decreased to 17.64±3.3°, which indicated that the hydrogel coating significantly enhanced the hydrophilicity of the PU surface, which laid the foundation for the excellent anti-fouling ability of the coating.
[0089] Fig. 9 The protein adsorption rate results of each sample showed that compared with bare PU, the protein adsorption rate on the surface of pSB SN hydrogel coating was only 17.09±3.39% of that of bare PU, while the protein adsorption rate on the surface of pSB DN hydrogel coating was less than 5%, indicating that its anti-protein adhesion ability was significantly improved.
[0090] The excellent anti-protein adhesion ability of PU modified with pSB hydrogel coating is mainly attributed to the strong repulsion between the hydration layer on the surface of zwitterionic polymer and protein, which weakens the interaction between protein and PU matrix surface.
[0091] (6) Durability of zwitterionic double network hydrogel coating
[0092] Ultrasound (300W) was used to accelerate the destruction of the coating to examine its stability. After one hour of ultrasonic destruction, the contact angle of the pSB DN hydrogel coating did not change significantly, indicating that the pSB DN hydrogel coating has good stability.
[0093] Example 2
[0094] Experimental steps:
[0095] (1) Preparation of zwitterionic double network hydrogel coating
[0096] The plasma-treated PU substrate was placed in a culture dish, immersed in a 7% (wt%) acetone solution of photoinitiator 2959 for 30 minutes, taken out, and rinsed alternately with ethanol and deionized water to remove the photoinitiator 2959 physically attached to the surface, thereby obtaining an initiator-treated PU film, which was named PU-2959.
[0097] PU-2959 was fixed in the mold using polyacrylate glue, and the first network pSB pregel solution (containing 1.2M SBMA, 3mol% MBA (relative to SBMA) and 0.15mol% photoinitiator 1173 (relative to SBMA)) was injected onto the PU-2959 substrate using a syringe, and then covered with a glass plate and clamped with tweezers. Under deoxygenated conditions, a UV lamp (302nm, 6W) was irradiated for 3h to form a pSB single network hydrogel coating on the surface of the PU-2959 substrate, which was recorded as pSB SN-PU.
[0098] The prepared pSB SN-PU was immersed in a second network pSB pregel solution (containing 4.5 M SBMA, 0.15 mol% MBA (relative to SBMA) and 0.01 mol% photoinitiator 1173 (relative to SBMA)) and stored at 4°C in the dark for 20 h. After being taken out, it was irradiated with an ultraviolet lamp (302 nm, 6 W) for 4 h under deoxygenated conditions to form a pSB double network hydrogel coating on the surface of the pSB SN-PU, which was recorded as pSB DN-PU.
[0099] Example 3
[0100] Experimental steps:
[0101] (1) Preparation of zwitterionic double network hydrogel coating
[0102] The plasma-treated PU substrate was placed in a culture dish, immersed in a 4% (wt%) acetone solution of photoinitiator 2959 for 20 minutes, taken out, and rinsed alternately with ethanol and deionized water to remove the photoinitiator 2959 physically attached to the surface, thereby obtaining an initiator-treated PU film, which was named PU-2959.
[0103] PU-2959 was fixed in the mold using polyacrylate glue, and the first network pSB pregel solution (containing 0.8M SBMA, 5mol% MBA (relative to SBMA) and 0.08mol% photoinitiator 1173 (relative to SBMA)) was injected onto the PU-2959 substrate using a syringe, and then covered with a glass plate and clamped with tweezers. Under deoxygenated conditions, a UV lamp (302nm, 6W) was irradiated for 5h to form a pSB single network hydrogel coating on the surface of the PU-2959 substrate, which was recorded as pSB SN-PU.
[0104] The prepared pSB SN-PU was immersed in a second network pSB pregel solution (containing 4MSBMA, 0.1 mol% MBA (relative to SBMA) and 0.008 mol% photoinitiator 1173 (relative to SBMA)) and stored at 4°C in the dark for 25 h. After being taken out, it was irradiated with an ultraviolet lamp (302 nm, 6 W) for 5 h under deoxygenated conditions to form a pSB double network hydrogel coating on the surface of the pSB SN-PU, which was recorded as pSB DN-PU.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a pure zwitterionic double network hydrogel coating, characterized in that: The steps include: After the substrate to be treated is treated with plasma, it is immersed in a hydrophobic photoinitiator solution for a set time, and then taken out and excess hydrophobic photoinitiator is washed off to obtain a pretreated substrate; The first network pSB pregel solution is covered on the surface of the pretreated substrate, and irradiated with ultraviolet light under deoxygenated conditions to form a pSB single network hydrogel coating on the surface of the substrate; Then, the substrate is immersed in the second network pSB pregel solution, stored at low temperature and away from light for a set time, taken out, and irradiated with ultraviolet light under deoxygenated conditions to form a pSB double network hydrogel coating on the surface of the substrate; In the first network pSB pregel solution, the concentration of SBMA is 0.5-1.5M, the molar percentage of MBA to SBMA is 1-5%; the molar percentage of hydrophilic photoinitiator to SBMA is 0.05-0.2%; In the second network pSB pregel solution, the concentration of SBMA is 2-5M, the molar percentage of MBA to SBMA is 0.05-0.15%, and the molar percentage of hydrophilic photoinitiator to SBMA is 0.005-0.02%.
2. The method for preparing the pure zwitterionic double network hydrogel coating according to claim 1, characterized in that: The hydrophobic photoinitiator is photoinitiator 2959 or benzophenone; Preferably, the concentration of the hydrophobic photoinitiator solution is 2-7 wt %; Preferably, the concentration of the hydrophobic photoinitiator solution is 4-6wt%; Preferably, the concentration of the hydrophobic photoinitiator solution is 5 wt %.
3. The method for preparing the pure zwitterionic double network hydrogel coating according to claim 1, characterized in that: The substrate to be processed is a medical device substrate; Preferably, the substrate to be treated is a medical catheter substrate; Preferably, the material of the medical guide rod substrate is polyvinyl chloride, polyurethane or silicone rubber.
4. The method for preparing the pure zwitterionic double network hydrogel coating according to claim 1, characterized in that: The substrate to be treated is immersed in the hydrophobic photoinitiator solution for 20-40 minutes; Preferably, after the substrate to be treated is immersed in the hydrophobic photoinitiator solution, it is rinsed alternately with ethanol and deionized water to remove the hydrophobic photoinitiator physically attached to the surface of the substrate to be treated.
5. The method for preparing the pure zwitterionic double network hydrogel coating according to claim 1, characterized in that: In the first network pSB pregel solution, the concentration of SBMA is 0.7-1.2M, the molar percentage of MBA to SBMA is 3-5%; the molar percentage of hydrophilic photoinitiator to SBMA is 0.07-0.15%; Preferably, in the first network pSB pre-gel solution, the concentration of SBMA is 1 M, the molar percentage of MBA to SBMA is 4%, and the molar percentage of hydrophilic photoinitiator to SBMA is 0.1%.
6. The method for preparing the pure zwitterionic double network hydrogel coating according to claim 1, characterized in that: The wavelength of the ultraviolet lamp is 250-350nm, preferably 300-320nm; Preferably, the UV lamp irradiation time is 2-5 hours, preferably 3-4 hours.
7. The method for preparing a pure zwitterionic double network hydrogel coating according to claim 1, characterized in that: In the second network pSB pregel solution, the concentration of SBMA is 3-5M, the molar percentage of MBA to SBMA is 0.07-0.12%; the molar percentage of hydrophilic photoinitiator to SBMA is 0.007-0.015%; Preferably, in the second network pSB pregel solution, the concentration of SBMA is 3.5-4.5M, the molar percentage of MBA to SBMA is 0.09-0.12%; the molar percentage of hydrophilic photoinitiator to SBMA is 0.009-0.012%; Preferably, in the second network pSB pregel solution, the concentration of SBMA is 4M, the molar percentage of MBA to SBMA is 0.01%, and the molar percentage of hydrophilic photoinitiator to SBMA is 0.01%.
8. The method for preparing the pure zwitterionic double network hydrogel coating according to claim 1, characterized in that: The storage temperature of the low-temperature storage setting time is lower than 5°C, and the storage time is 15-30 hours, preferably 20-25 hours.
9. A pure zwitterionic double network hydrogel coating, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.
10. A medical device, characterized in that: The pure zwitterionic double network hydrogel coating of claim 9 is attached to its surface; Preferably, the medical device is a medical device that comes into contact with blood.
Citation Information
Cited By
Radiation preparation method and application of zwitter-ion hydrogel
CN121895596A